Thorstein Veblen and His Critics, 1891-1963 : Conservative, Liberal, and Radical Perspectives. - Tilman, Rick (Princeton legacy library., 2014)
The influential economist and philosopher Thorstein Veblen (1857-1929) was one of the most original and penetrating critics of American culture and institutions, and his work attracted and still attracts the attention of scholars from a wide range of political viewpoints and scholarly disciplines. Focusing on the doctrinal and theoretical facets of Veblen's political economy, this book offers a study not only of his ideas but also of the way his critics have responded to them. Rick Tilman assesses the weight of the critics' reactions, both positive and negative, as well as exposing their so.